Distributed Gaussian orbitals for molecular calculations: application to simple systems. (16th February 2020) - Battaglia, Stefano; Bouet, David; Lecoq, Alexis; Evangelisti, Stefano; Faginas-Lago, Noelia; Leininger, Thierry; Lombardi, Andrea
ABSTRACT: In this article, the possible use of sets of basis functions alternative with respect to the usual atom-centred orbitals sets is considered. The orbitals describing the inner part of the wavefunction (i.e. the region close to each nucleus) are still atomic Gaussian functions: tight Gaussian orbitals having different angular momenta and large exponential coefficients, centred on each nucleus. On the other hand, the outer part of the wavefunction is described through a set of s -type distributed Gaussian orbitals: s -type Gaussians having a unique fixed exponent, and whose fixed centres are placed on a uniform mesh of points evenly distributed in the region surrounding all the atoms of the molecule. The resulting basis sets are applied to various one-electron systems in order to assess the capability to describe different types of one-electron wavefunctions. Moreover, the hydrogen atom and the dihydrogen cation, for which accurate solutions exist, are also considered for comparison, to assess the effectiveness of the proposed approach. Preliminary results concerning the treatment of electron correlation, necessary for a quantitatively correct description of many-electron atoms and molecules, are also presented. GRAPHICAL ABSTRACT: